6. Iannis Xenakis’s Free Stochastic Music Program as an Aid to Analysis - Ronald Squibbs (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
In 1962, Xenakis composed five works with the assistance of a computer program that he titled Free Stochastic Music. Xenakis provided the code for the program, as well as other documentation required to produce output, in Formalized Music and elsewhere. As with any computer program, the best way to understand its operation is to run it and to test its output against one’s expectations. Despite the documentation that Xenakis provided, it is not possible to run Free Stochastic Music on modern compilers without editing its code for compatibility. Even after this obstacle has been overcome, interpretation of the output requires some knowledge of the theoretical principles on which the stochastic compositional algorithm at the heart of the program was based. This chapter aims to provide a concise explanation of the operation of the program, using as input the data that Xenakis provided for the composition of Atrées. A musical transcription of some newly generated output is then tested for consistency with the program’s theoretical premises, as will the first movement of Atrées. Special emphasis is given to the crucial roles of texture and instrumentation in generating the characteristic sound of this repertoire.